Polymer Materials for Drug Delivery and Tissue Engineering - Hudita, Ariana; Gǎlǎţeanu, Bianca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint, devoted to the topic of "Polymer Materials for Drug Delivery and Tissue Engineering", gathers a multidisciplinary collection of articles that merge the knowledge and expertise of worldwide researchers who present their latest research in the field of polymer-based materials. This reprint brings together articles that report original research on the design and synthesis of novel drug delivery systems and scaffolds or highlight insights into polymer interactions.